Kepatuhan Minum Tablet Tambah Darah dan Kejadian Anemia Pada Remaja - Siti Asiyah (STIKES dan AKZI Karya Husada Kediri, 2023)
Adolescent girls are one of the groups that are prone to anemia. The cause of iron deficiency in young women is that they are often identical to maintaining appearance, the desire to stay slim or thin so that they diet and eat less. The aim of the study was to analyze adherence and anemia in adolescents. This research is an analytical survey research with a quantitative approach. The design used is Cross Sectional. This study tries to find out whether there is a relationship between adherence to taking Fe tablets with the incidence of anemia in young women at SMK Sunan Giri Mulung Village in 2022. The population is all teenage girls in Class X and XI at SMK Sunan Giri Mulung Village, which is as many as 89 students. The sample is some young women X and XI totaling 73 students. Based on the results of the chi-square test, it is known that the P value <0.00, then Ha is accepted, meaning that there is a relationship between adherence to taking blood-added tablets and the incidence of anemia. Adherence is a form of behavior that arises as a result of the interaction between health workers and patients so that patients understand the plan with all its consequences and agree to the plan and implement it. With adherence to taking tablets with high blood pressure, young women will avoid anemia.